Protozoan Parasites Glycosylphosphatidylinositol Anchors: Structures, Functions and Trends for Drug Discovery - Morotti, Ana Luísa Malaco; Martins-Teixeira, Maristela B.; Carvalho, Ivone (Current Medicinal Chemistry, 2019)
Background: Glycosylphosphatidylinositol (GPI) anchors are molecules located on cell membranes of all eukaryotic organisms. Proteins, enzymes, and other macromolecules which are anchored by GPIs are essential elements for interaction between cells, and are widely used by protozoan parasites when compared to higher eukaryotes. Methods: More than one hundred references were collected to obtain broad information about mammalian and protozoan parasites’ GPI structures, biosynthetic pathways, functions and attempts to use these molecules as drug targets against parasitic diseases. Differences between GPI among species were compared and highlighted. Strategies for drug discovery and development against protozoan GPI anchors were discussed based on what has been reported on literature. Results: There are many evidences that GPI anchors are crucial for parasite’s survival and interaction with hosts’ cells. Despite all GPI anchors contain a conserved glycan core, they present variations regarding structural features and biosynthetic pathways between organisms, which could offer adequate selectivity to validate GPI anchors as drug targets. Discussion was developed with focus on the following parasites: Trypanosoma brucei, Trypanosoma cruzi, Leishmania, Plasmodium falciparum and Toxoplasma gondii, causative agents of tropical neglected diseases. Conclusion: This review debates the main variances between parasitic and mammalian GPI anchor biosynthesis and structures, as well as clues for strategic development for new anti-parasitic therapies based on GPI anchors.
Keywords: lipopeptidophosphoglycans (LPPGs)